2006
DOI: 10.1159/000095228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of the 11q13 amplicon in head and neck squamous cell carcinoma

Abstract: Amplification of 11q13 DNA sequences and overexpression of CCND1 are common findings in head and neck squamous cell carcinoma (HNSCC), identified in about 30% of the cases. However, little is known about initiation of the amplification and the organization of the amplicon. In order to study the structure of the amplicon in more detail and to learn more about the mechanisms involved in its initiation, prometaphase, metaphase, and anaphase fluorescence in situ hybridization (FISH) with 40 BAC clones spanning a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
5
20
0
Order By: Relevance
“…Previously, we have identified 11q13, including overexpressed FADD and PPFIA1, as one of the most commonly and highly amplified regions in LSCC (Järvinen et al, 2006). The amplification mechanism and potential target genes of 11q13 have been studied extensively in HNSCC (e.g., Snijders et al, 2005;Jin et al, 2006;Gibcus et al, 2007a). For example, in line with our data, Huang et al (2006) recently showed that multiple genes at the 11q13 amplicon core (spanning from TPCN2 to SHANK2) were overexpressed in amplified OSCC tumors and cell lines.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previously, we have identified 11q13, including overexpressed FADD and PPFIA1, as one of the most commonly and highly amplified regions in LSCC (Järvinen et al, 2006). The amplification mechanism and potential target genes of 11q13 have been studied extensively in HNSCC (e.g., Snijders et al, 2005;Jin et al, 2006;Gibcus et al, 2007a). For example, in line with our data, Huang et al (2006) recently showed that multiple genes at the 11q13 amplicon core (spanning from TPCN2 to SHANK2) were overexpressed in amplified OSCC tumors and cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…In concordance with our data, Snijders et al (2005) detected narrow amplifications at 6q12 (PTP4A1, EGFL11), 9p13.3 (TLN1), 9p24.1 (UHRF2, JMJD2C, PTPRD), and 11p13 (CD44, FJX1, TRAF6) in oral SCC (OSCC) using BAC arrays and confirmed the expression levels of selected genes using Q-RT-PCR. Additionally, high-level amplification at 11q13 has been identified in a number of studies (e.g., Snijders et al, 2005;Jin et al, 2006;Järvinen et al, 2006;Gibcus et al, 2007a). Thus, our as well as previous data show that high-level amplifications are recurrent in HNSCC and are likely to contain genes with pathogenetic relevance in the disease.…”
Section: Discussionsupporting
confidence: 83%
“…Although CCND1 is considered to be the main tumor-promoting gene in this amplicon, it does not have predictive value for the survival of HNSCC and breast cancer patients (8,(11)(12)(13)(14). The 11q13 amplicon harbors several independent amplification cores, indicating the presence of additional driving oncogenes in this region (6,15,16,34). The calcium-activated chloride channel ANO1, located within the 11q13 amplicon, is known to be overexpressed in several cancers and recently has been reported to promote oncogenesis in HNSCC by activating MAPK (28).…”
Section: Ano1 Regulates Egfr-and Calcium-dependent Signaling Pathwaysmentioning
confidence: 99%
“…Although cyclin D1 (CCND1) has been considered to be the main driver of the 11q13 amplicon (8)(9)(10), it is not sufficient for malignant transformation of normal breast cells and lacks predictive value for the survival of head-and-neck squamous cell carcinoma (HNSCC) or breast cancer patients (8,(11)(12)(13)(14). Instead, the region has been shown to harbor several independent amplification cores, indicating that other genes could be potential driving oncogenes (6,15,16). Fine mapping of 11q13 in HNSCC led to the identification of another gene in this amplicon, anoctamin-1 (ANO1).…”
mentioning
confidence: 99%
“…Oral cancer overexpressed 1 (ORAOV1) was earlier reported to be involved in ESCC and validated at the mRNA level. 60 Overexpression of ORAOV1 was reported in head and neck squamous cell carcinoma (HNSCC). 61 Oral cancer overexpressed 2 (ORAOV2) is another member of the same family, which is a transmembrane protein reported to be involved in HNSCC, oral squamous cell carcinoma and gastrointestinal stromal tumors but has not been described in ESCC.…”
Section: Genes Overexpressed In Esccmentioning
confidence: 99%